The effect of addition of LDPE on the melting and crystallization characteristics of pigmented PP - Mokhtar, Munirah (Faculty of Chemical & Natural Resources Engineering, 1994)
Blends of PP pigmented with red iron oxide and LDPE were prepared by melt mixing in an injection molder. The thermal characteristics of the blends were analyzed using DSC. The blends were completely immiscible as shown by the presence of two distinct melting and crystallization peaks. The melting point of PP decreased with increasing content of PE whereas that of PE was not much affected. The crystallization transitions of PP (T onset and Tc) shifted toward higher temperatures which showed that both PE and iron oxide acted as nucleating sites for PP. The overall crystalinity of both PP and PE decreased with increasing content of the other polyolefin components. Such effect was due to the kinetic and thermodynamic effects as well as to different rates of crystallization.